2014
DOI: 10.1021/jf404624h
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Aluminum with Biochars and Oxidized Biochars: Implications for the Biochar Aging Process

Abstract: Interactions of aluminum with primary and oxidized biochars were compared to understand the changes in the adsorption properties of aged biochars. The structural characteristics of rice straw-derived biochars, before and after oxidation by HNO3/H2SO4, were analyzed by element composition, FTIR, and XPS. The adsorption of Al to primary biochars was dominated by binding to inorganic components (such as silicon particles) and surface complexation of oxygen-containing functional groups via esterification reactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
97
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(105 citation statements)
references
References 44 publications
8
97
0
Order By: Relevance
“…Once acid was applied to the biochar, solid phase carbonate in the biochar may have dissolved, increased pH (due to formation of HCO 3 − ), and induced metal precipitation within the solution and to the biochar. The eucalyptus biochar had 4% CaCO 3 ( Table 1), therefore some protons will also be neutralised by carbonates [44,45], although we adjusted to a set pH in the experiments. In summary, the results suggest that biochar has potential for metal and proton removal over a wide range of soluble metal concentrations, as they may occur in drainage channels of acidic ASS, which is in agreement with our previous studies [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Once acid was applied to the biochar, solid phase carbonate in the biochar may have dissolved, increased pH (due to formation of HCO 3 − ), and induced metal precipitation within the solution and to the biochar. The eucalyptus biochar had 4% CaCO 3 ( Table 1), therefore some protons will also be neutralised by carbonates [44,45], although we adjusted to a set pH in the experiments. In summary, the results suggest that biochar has potential for metal and proton removal over a wide range of soluble metal concentrations, as they may occur in drainage channels of acidic ASS, which is in agreement with our previous studies [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…The surface functionality can be characterized by X-ray photoemission spectroscopy (XPS), FTIR, and temperature programmed desorption (TPD) techniques [28][29][30]. The detailed surface chemistry of biochar, surface functionalities, and composition can be obtained from these technologies.…”
Section: Surface Functionality Characterizationmentioning
confidence: 99%
“…Although Al is typically in solution below pH 5.5, once in solution it is able to complex with organic and inorganic compounds. A recent study demonstrated that trivalent Al complexes with rice-straw derived biochars [17], and that the presence of silicon increased surface complexation. Because grasses typically contain more silicon than wood, our observation that KB-sourced biochar is more effective at lowering Al root concentrations than wood-sourced biochar may be attributable to fundamental biochar properties rather than a simple attenuation of pH.…”
Section: Discussionmentioning
confidence: 99%